Challenges in navigating the education-migration pathways, and subjective well-being of highly educated immigrants: the case of Indian student immigrants in the United Kingdom - Udayanga, Samitha (Frontiers in Sociology, 2024)
Migration is generally considered to be a driver of enhancing the subjective well-being of immigrants; however, personal characteristics such as educational attainment, migration channel, and country of origin may moderate the impact of immigrant life on expected well-being. Therefore, the present study aimed to explore the intersections between the lived experiences of post-secondary Indian immigrant students in the United Kingdom (UK), the challenges they encounter as immigrants, and how these experiences could impact their subjective well-being. A qualitative research design was employed, which included a focus group discussion and 24 in-depth interviews with postgraduate students who had migrated from India to the United Kingdom. Four themes generated from the thematic analysis, which overall indicated that individuals who came to the United Kingdom as international students to study, work, and settle over time often found themselves unable to leverage their educational credentials to establish expected subjective well-being. This was primarily due to the systematic denial of their agency (capability) to overcome challenges in the host society. Reasons include becoming involuntarily immobile in the host country, incongruency between past expectations and present experiences and prospects, socio-emotional and financial costs associated with immigrant life that hinder the freedom of agency, and bureaucratic burdens. All these reasons can generate an unconducive environment for those immigrants who took part in the study, ultimately decreasing their life satisfaction and positive feelings while increasing negative feelings. In conclusion, the findings question the widely held belief that migration can increase subjective well-being and describe how migration comes at a cost, along with several other challenges, particularly for those who have moved first to learn, secondly to earn, and then to settle in. The channel of migration (migration for education and then to settle in) thus plays a crucial role in determining the outcomes of migration while influencing the anticipated subjective well-being of migrants.